External Application of a Xiaozhen zhiyang Decoction for Facial Rash Related to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors in Chinese Patients: A Prospective Single-Arm Observational Study - Jietao Lin MD; Lingling Sun MD; Jing Zhang MM; Ke Zhu MD; Hanrui Chen MD; Xinting Zhen MD; Yang Cao MD; Siyu Wang MD; Lizhu Lin MD (Integrative Cancer Therapies)
Background: Evidence regarding Chinese herbal medicine for facial rash related to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is limited. Therefore, this study aimed to investigate whether ex ternal application of a Xiaozhen zhiyang (XZZY) decoction is effective for EGFR-TKI-related facial rash in Chinese patients. Methods: In this prospective cohort study, 123 participants with EGFR-TKI-related facial rash were recruited from July 18, 2019 to May 20, 2021. The intervention was external application of the XZZY decoction twice daily for 2 weeks using a facial mask. Treatment efficacy, change in the WoMo score, and quality of life were evaluated as endpoints. Results: The average age of the 123 enrolled participants was 54.83 ± 12.45 years, and 48.78% were female. The total efficiency of treatment was 93.5%, including 12 (10%) cases were cured, 20 (16.26%) cases were markedly improved and 83 (67.48%) cases were improved. The generalized estimating equations showed decreased WoMo scores, itching, and pain, as well as an improved quality of life after the treatment. Only 1 participant reported skin allergies, and no other adverse effects were reported. Conclusion: This study showed the effectiveness and safety of a XZZY decoction for EGFR-TKI-related rash.